THE CYANOGENIC POTENTIAL OF ROOTS AND LEAVES OF NINETY NINE CASSAVA CULTIVARS - A. Hidayat; N. Zuraida; I. Hanarida (Indonesian Agency for Agricultural Research and Development, 2002)
Studies on cyanogenic potential (CP) of roots and leaves of Indonesian cassava germplasm are still inadequate in relation to food toxicity and on human health. The CP of leaves of 99 cassava cultivars was analyzed using picrate paper kits. Effort to reduce CP of cassava leaves by boiling them was also conducted. The results showed that roots and leaves had low and moderate level of CP. There was a significant correlation between the CP of leaves (Y) and roots (X) of 45 cassava cultivars with regression equation Y = 36.214 + 1.3085 X (r = 0.5228). The CP content was high in the young leaves (241 ppm) and low in the older ones (99 ppm). The proximal portion of the roots had the highest CP content (300 ppm), and that in the distal end was the lowest (56 ppm). The root part close to cortex had highest CP content (550 ppm), whereas the central part was the lowest (35 ppm). Boiling cassava leaves for 20 minutes significantly reduced the CP up to 75%, indicating that for safety, cassava should be completely processed or cooked. This study implied that CP content should be considered in cassava breeding programs. Forty two of 99 cassava cultivars have CP below 50 ppm which is safe for consumption.